The effect of two active learning strategies on the expressive performance of fourth-grade literary students (Journal of the College of Basic Education, 2022)
This research aims to study (The Impact of Two Strategies of Active Learning on Comprehension Performance of the Fourth Literary Stage), and to certify the goal of this research, the following hypotheses have been put forward: there is no statistically significant difference between the average scores of the experimental group students who are taught according to cooperative learning method and the average scores of the second group students who are taught according to discussion and active dialogue and the control group students who are taught according to the traditional method. The researcher chooses all secondary and preparatory morning studies schools fourth literary students in Hilla in Babylon City. The researcher intentionally chooses (84) students distributed over three classes. The research tool includes (12) writing topics which are agreed upon and tested by experts. The researcher has adopted the following statistical methods: Test (F) for two independent samples, Pearson's correlation equation, One way Analysis of Variance, and (Chi- Square). After correcting the answers and processing the data statistically using statistical bag (SPSS), the results show that: there is a statistically significant difference among the average of comprehension performance of the three research groups and thus the first main hypothesis is refused. Accordingly, the researcher verifies the three sub hypotheses. Scheffe test, for subsequent comparisons, is applied to figure out the direction of the difference among the three research groups and the results have been embodied and in the light of these results, the researcher has concluded the following:The employment of the two strategies viz., the cooperative learning and the discussion and active dialogue are effective in the development of comprehension performance of the Fourth Literary Stage in comparison with the traditional methods. In addition, the researcher has recommended the following:Schools administrations should advise educational staff to create and spread an atmosphere of democracy and freedom and make schools appeal to students when teaching comprehension subjects and adapt the new teaching strategies. The specialized supervision in Directorate general of education/Babylon should increase their interests to educational staff and advise them to use the strategies of cooperative learning and discussion and active dialogue when they teach comprehension.